Constructing Branching Trees of Geostatistical Simulations - Valencia, J (SPRINGER HEIDELBERG, 2022)
This paper proposes the use of multi-stage stochastic programming with recourse for optimised strategic open-pit mine planning. The key innovations are, firstly, that a branching tree of geostatistical simulations is developed to take account of uncertainty in ore grades, and secondly, scenario reduction techniques are applied to keep the trees to a manageable size. Our example shows that different mine plans would be optimal for the downside case when the deposit turns out to be of lower grade than expected compared to when it is of higher grade than expected. Our approach further provides the probabilities of these outcomes; that is, the idea is to move toward adaptive mine planning rather than just producing a single mine plan.